The impact of ai learning tools on ESL learners' motivation and success: A systematic literature review - Ihsan Ahmed; Abdul Ghafoor; Deemimah Liliuara; Vina Qurrota’ Akyuningrum (English Learning Innovation, 2025)
This review identifies key trends and findings on the effectiveness of Artificial intelligence chatbots, e.g., ChatGPT and other AI tools adaptive teaching things, and language gratitude systems in successful English as a second language achievement by examining 35 articles published after 2022. The results showed that Artificial Intelligence (AL) can increase students’ motivation if they have up-to-date information abilities, actual period feedback, and gamified features that advance with intrinsic and extrinsic motivation. Artificial Intelligence (AI) chatbots facilitate personality teaching and separate responses, improving language skills. The article also highlights technical availability, humanoid communication, and overdependence on artificial intelligence (AI). The analysis recommends developments for integrating these technologies into English teaching and emphasizes significant investigation gaps in awareness of the long-term effect of AI implementations on language knowledge.